Phosphaturic mesenchymal tumor: Clinicopathological features with outcomes in 10 patients with review of literature - Vivek C. Parameshwar; Bharat Rekhi; Ashwini Duggad; Mukta Ramadwar (Indian Journal of Pathology and Microbiology)
Background: Phosphaturic mesenchymal tumors (PMTs) are rare mesenchymal tumors, associated with long-standing, non-specific but often debilitating symptoms in the affected patients. These tumors display characteristic histopathological features and in case, identified timely, can be a boon for patients, given an excision is completely curative. Aims: To evaluate the clinical and histopathological features of 10 PMTs, diagnosed at our institution, along with clinical outcomes in those patients. Materials and Methods: This was a retrospective study, wherein 10 PMTs, diagnosed from January 2013 to July 2022, were included. Results: The average age at the time of diagnosis was 40 years with an M:F ratio of 4:1. Clinical features included lumps, weakness, bone pain, difficulty in moving and walking, and pathologic fractures. The biochemical analysis showed normal serum calcium levels (average = 9.5 mg/dL), with low serum phosphorus (average = 2.2 mg/dL) and raised serum fibroblast growth factor 23 (FGF23) levels, in all the cases, wherever available. On histopathology, all tumors showed cells arranged in a hemangiopericytomatous pattern, including oval to short spindle forms. Multinucleate giant cells were present in nine tumors, and characteristic “grungy calcifications” was observed in eight tumors. Prominent pseudo cystic spaces were seen in eight tumors. A significant number of mitotic figures and tumor necrosis were not seen in any tumor. In five cases where follow-up was available, there was complete resolution of symptoms post-resection with no recurrence or metastasis. All those patients were free of disease until the last follow-up. Conclusion: This constitutes the first largest comprehensive study on these rare tumors from our country. PMTs can be diagnosed based on certain histopathological features and correlation with clinicoradiological and biochemical findings. These are invariably benign neoplasms. Patients are relieved of their debilitating symptoms after adequate surgical tumor resection. Therefore, their correct and timely diagnosis is crucial.